RELATIONSHIP BETWEEN NURSE MOTIVATION AND PREVENTION ACTIONS (HAIs) IN ICU AND HCU ROOMS - Irpan Ali Rahman; Rian Hermawan; Lilis Lismayanti; Adi Nurapandi; Asep Gunawan (Jurnal Ilmiah Keperawatan, 2023)
Nosocomial infections are a real problem worldwide and are increasing. The consequences are very detrimental to the patient, in addition to the number of days spent in the hospital, and the cost of treatment increases to the point of causing death. Nurses play an important role in the prevention of healthcare-associated infections (HAIs) because nurses are a healthcare team that deals directly with patients and infectious materials. Motivation for nurses is increasingly important because managers distribute work to be done well and integrated into the desired goals. This study aims to determine the relationship between nurse motivation and preventive action (HAIs) in the ICU, and HCU. Method: research that is quantitative analytic using a cross-sectional approach. The population in this study was 24 nurses in the ICU and HCU. Samples were taken using the total sampling technique. Results: the study showed that the motivation of the nurses was mostly in the good category by 19 people (79.2%), the preventive actions (HAIs) were mostly in the good category by 18 people (75%) and there was a significant relationship between the motivation of the nurses and the prevention of healthcare-associated infections (HAIs) in the ICU Room, HCU Pandega Hospital in 2022 because the value α > ρ value (0.05 > 0.001) and the chi-square value (χ2) count > chi-square (χ2) table (10.189 > 3.841). Conclusion: there is a significant relationship between nurse motivation and action (HAIs).